Assessing the Moderating Effect of the End User in Consumer Behavior: The Acceptance of Technological Implants to Increase Innate Human Capacities - Pelegrín-Borondo, Jorge; Reinares-Lara, Eva; Olarte-Pascual, Cristina; Garcia-Sierra, Marta (Frontiers in Psychology, 2016)
Today, technological implants are being developed to increase innate human capacities, such as memory or calculation speed, and to endow us with new ones, such as the remote control of machines. This study’s aim was twofold: first, to introduce a Cognitive-Affective-Normative model of technology acceptance to explain the intention to use this technology in the field of consumer behavior; and second, to analyze the differences in the intention to use it based on whether the intended implant recipient is oneself or one’s child (i.e., the moderating effect of the end user). A multi-group analysis was performed to compare the results between the two groups: implant “for me” (Group 1) and implant “for my child” (Group 2). The model largely explains the intention to use the insideable technology for the specified groups (variance explained (R2) of over 0.70 in both cases). The most important variables were found to be “positive emotions” and (positive) “subjective norm.” This underscores the need to broaden the range of factors considered to be decisive in technology acceptance to include variables related to consumers’ emotions. Moreover, statistically significant differences were found between the “for me” and “for my child” models for “perceived ease of use” and “subjective norm.” These findings confirm the moderating effect of the end user on new insideable technology acceptance.